The Oxford handbook of the study of religion - Stausberg, Michael; Engler, Steven (Oxford University Press, 2017)
This Handbook offers an authoritative and up-to-date survey of original research in the study of religion. It's organised into seven systematic parts: "Religion"; "Theoretical Approaches"; "Modes"; "Environments"; "Topics"; "Processes"; and "The Discipline".
Published online in "Oxford Handbooks Online" in June 2017
Keywords: Aufsatzsammlung; Religionswissenschaft